Performance assessment of water vortex power plant: Effect of material type and blade number - Hussein M. Zainal; Omer K. Ahmed (Results in Engineering)
This article aims to evaluate the performance of water vortex power plants by studying the effect of turbine material type, number of blades, and height to enhance the efficiency of sustainable energy generation using turbine systems. The research used an experimental model to simulate an operating environment similar to turbine power plants. The experiment included the use of turbines made of carbon alloys and galvanized alloys, with variable numbers of blades (four blades and six blades) and different heights from the bottom of the basin (1.5 cm, 3 cm, 5 cm, and 8 cm). The rotation rates and resulting force were measured on both sides of the turbine, and the system efficiency was calculated using accurate measuring tools to ensure the reliability of the results. The results showed that the type of turbine material, number of blades, and turbine height directly affect the performance. For example, a turbine made of carbon alloy with four blades and a height of 3 cm achieved a rotation speed of 89 rpm, a generated force of 15.67 N, and an efficiency of 68.6 %. In contrast, the six-blade turbine under the same conditions showed a higher rotation speed of 100 rpm, but the efficiency dropped to 64 %. These results highlight that increasing the number of blades can enhance the rotation speed but may decrease efficiency, reflecting the importance of balancing design and function to achieve optimal performance.